Treatment Options in Congenital Disorders of Glycosylation - Park, Julien H.; Marquardt, Thorsten (Frontiers in Genetics, 2021)
Despite advances in the identification and diagnosis of Congenital disorders of glycosylation (CDG), treatment options remain limited and are often constrained to symptomatic management of disease manifestations. However, recent years have seen significant advances in treatment and novel therapies aimed both at the causative defect and secondary disease manifestations have been transferred from bench to bedside. In this review, we aim to give a detailed overview of the available therapies and rising concepts to treat these ultra-rare diseases.